Heritage of Islamic ethics and contemporary issues: a call for relevantization - Malik, Mohammad Manzoor (International Islamic University Malaysia (IIUM), 2011)
This study addresses the subject of Islamic ethics from definitional and disciplinary perspectives. It highlights the need for relevantization of Islamic ethics to contemporary issues in a systematic manner which, in turn, calls for development of Islamic ethics as a complete discipline with ability to meet all types of challenges: conceptual, practical, normative, applicative, etc. Regarding the definitional issue, different from and more expansive than the traditional understanding of al-ākhlāq, the researcher argues that a proper definition of ethics should include ethically relevant habits, character, and behavior in its subject matter. As an academic discipline of paramount, practical significance, Islamic ethics should adequately address metaethical, normative, and applicative aspects of the subject. In terms of metaethics, Islamic ethics is derived from revealed knowledge; whereas, principles of Islamic jurisprudence (uṣūl al-fīqh) offers the best available methodology for the discipline in meeting demands of normativity and application. Regarding the nature of the subject of Islamic ethics, the researcher argues that understanding Islamic ethics as virtue ethics is unjustifiable reduction because a careful study of the subject from its sources would prove that Islamic ethics is rather an integrated field comprising of virtues ethics, divine command theory, duty-based ethics, etc. Therefore, Islamic ethics should be developed, taught, and learned as a whole composite of above-mentioned elements.